Hydrated Deep Eutectic Electrolytes for High‐Performance Zn‐Ion Batteries Capable of Low‐Temperature Operation. (19th December 2021) - Lin, Xidong; Zhou, Guodong; Robson, Matthew J.; Yu, Jing; Kwok, Stephen C. T.; Ciucci, Francesco
Abstract: Aqueous Zn‐ion batteries (ZIBs) are a promising energy storage technology due to their intrinsic safety, eco‐friendliness, and cost‐effectiveness. However, aqueous electrolytes generally induce parasitic interfacial reactions (e.g., dendrite growth and passivation) that degrade the Zn metal anode, shortening ZIBs lifespan. This study develops a novel hydrated deep eutectic electrolyte (DEE), containing sulfolane (SL) and Zn(ClO4 )2 ·6H2 O, to prevent water‐induced deterioration. The strong coordination between SL and Zn 2+ triggers the deep eutectic effect, extending the operating temperature window of the DEE. The unique water‐in‐DEE structure boosts ionic diffusion, promotes Zn 2+ deposition, and reduces water reactivity, as revealed by in‐depth simulations and experiments. The developed DEE suppresses dendrite formation, allowing the Zn|DEE|Zn symmetrical cells to cycle over thousands of hours without short‐circuiting. With a polyaniline (PANI) cathode, Zn|DEE|PANI cells can cycle 2500 times with a capacity of 72 mAh g −1 at 3 A g −1 at room temperature and 500 times with 73 mAh g −1 at 0.3 A g −1 at −30 °C. The newly developed DEE significantly is a step forward for inexpensive, stable, and high‐performance ZIBs. Abstract : A hydrated deep eutectic electrolyte (DEE) using sulfolane (SL) and Zn(ClO4 )2 ·6H2 O is developed for a stable Zn‐ion battery. The strong coordination between SL and Zn 2+ triggers the deep eutectic effect, endowing DEE with a wide operating temperature window ranging from −40 °C to room temperature. The DEE is inexpensive, nonflammable, and allows excellent stability for Zn|DEE|polyaniline full cell.